NLR (Neutrophil-To-Lymphocyte Ratio), MLR (Monocyte-To-Lymphocyte Ratio) and NMLR (Neutrophil-Monocyte-To-Lymphocyte Ratio) as Biomarkers for Establishing the Diagnosis of Tuberculosis in Children - Nindy Putri Ferisa; Wisman Dalimunthe; Winra Pratita; Juliandi Harahap; Mahrani Lubis; Fathia Meirina (Indonesian Journal of Global Health Research, 2026)
Tuberculosis (TB) in children presents a major diagnostic challenge due to the paucibacillary nature of the infection and difficulties in sputum collection. As an alternative, blood cell ratios such as Neutrophil-to-Lymphocyte Ratio (NLR), Monocyte-to-Lymphocyte Ratio (MLR), and Neutrophil-Monocyte-to-Lymphocyte Ratio (NMLR) have been proposed as hematological biomarkers that can support the diagnosis of TB in children. This study aimed to evaluate the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of NLR, MLR, and NMLR in establishing the diagnosis of TB in children at RS Adam Malik. A retrospective observational study was conducted using data from the TB DOTS medical records of children aged 0–18 years during 2024. Hematologic parameters (neutrophils, monocytes, lymphocytes) and the ratios NLR, MLR, and NMLR were analyzed and compared with clinical and bacteriological TB diagnosis (TCM/BTA). Of the 219 children who met the inclusion criteria, NLR showed a sensitivity of 82.3%, specificity of 78.7%, PPV of 84.9%, NPV of 75.3%, and accuracy of 80.8%. MLR showed a sensitivity of 80.8%, specificity of 75.3%, PPV of 82.7%, NPV of 72.8%, and accuracy of 78.5%. NMLR showed a sensitivity of 76.9%, specificity of 66.3%, PPV of 76.9%, NPV of 66.3%, and accuracy of 72.6%. These ratios were significantly associated with TB diagnosis (p < 0.05). The most common clinical symptoms found in positive cases included persistent cough, prolonged fever, weight loss, and night sweats. NLR, MLR, and NMLR demonstrate good diagnostic value in supporting the diagnosis of TB in children. NLR showed the most optimal results, followed by MLR and NMLR. These hematological ratios can be used as quick, inexpensive, and easily accessible diagnostic aids, especially in facilities with limited bacteriological testing capabilities.